Meaning of Folklore The Analytical Essays of Alan Dundes - Dundes, Alan (Utah State University Press, 2007)
The essays of Alan Dundes virtually created the meaning of folklore as an American academic discipline. Yet many of them went quickly out of print after their initial publication in far-flung journals. Brought together for the first time in this volume compiled and edited by Simon Bronner, the selection surveys Dundes's major ideas and emphases, and is introduced by Bronner with a thorough analysis of Dundes's long career, his interpretations, and his inestimable contribution to folklore studies. Runner-up, the Wayland Hand Award for Folklore and History, 2009